Performing Robert Burns : enactments and representations of the 'National Bard' - Brown, Ian; Carruthers, Gerard (Edinburgh University Press, 2021)
This book is unashamedly aimed at a wider market than the ordinary academic volume, as it seeks to extend the impact of the research it contains, making it available to the worldwide community of Burns enthusiasts, without compromising on scholarship.